2013 IEEE Information Theory Workshop (ITW) 2013
DOI: 10.1109/itw.2013.6691349
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian half-duplex relay networks: Improved gap and a connection with the assignment problem

Abstract: Abstract-This paper studies a Gaussian relay network, where the relays can either transmit or receive at any given time, but not both. Known upper (cut-set) and lower (noisy network coding) bounds on the capacity of a memoryless full-duplex relay network are specialized to the half-duplex case and shown to be to within a constant gap of one another. For fairly broad range of relay network sizes, the derived gap is smaller than what is known in the literature, and it can be further reduced for more structured n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…As mentioned earlier, the result of this paper proves our original conjecture in [7] for Gaussian SISO networks for any number N of relays. Our framework also immediately extends to Gaussian networks with MIMO relays and independent noises since also in this setting independent inputs at all nodes are optimal in the cut-set upper bound to within a constant gap for all choices of the channel matrices.…”
Section: Examplessupporting
confidence: 83%
See 1 more Smart Citation
“…As mentioned earlier, the result of this paper proves our original conjecture in [7] for Gaussian SISO networks for any number N of relays. Our framework also immediately extends to Gaussian networks with MIMO relays and independent noises since also in this setting independent inputs at all nodes are optimal in the cut-set upper bound to within a constant gap for all choices of the channel matrices.…”
Section: Examplessupporting
confidence: 83%
“…In [6], Brahma et al's conjecture was proved for Gaussian HD diamond networks with N ≤ 6 relays; the proof is based on certain properties of submodularity and on linear programming duality; the proof technique does not appear to easily generalize to an arbitrary N . Our numerical experiments in [7] showed that Brahma et al's conjecture on the existence of optimal simple schedules for diamond HD relay networks extends to any Gaussian HD multi-relay network (i.e., not necessarily with a diamond topology) with N ≤ 8; we conjectured that the same holds for any N . Should our more general version of Brahma et al's conjecture be true, then Gaussian HD multi-relay networks have optimal simple schedules irrespectively of their topology.…”
Section: Introductionmentioning
confidence: 50%
“…In a preliminary version of this work [1], by using a bounding technique as in [26, pages 20-5, 20-7] we obtained GAP ∼ = N + 2 2 log (4(N + 2)) bits.…”
Section: Capacity To Within a Constant Gapmentioning
confidence: 99%
“…In a HD relay network with N = 2, we have 4 possible states that may arise with probabilities λ j with j ∈ [1,4]. We let λ 1 = λ 00 , λ 2 = λ 01 , λ 3 = λ 10 and λ 4 = λ 11 , where λ ij = P[S 1 = i, S 2 = j] ≥ 0, (i, j) ∈ {0, 1} 2 , such that λ 00 + λ 01 + λ 10 + λ 11 = 1.…”
Section: Appendix C Proof Of Theoremmentioning
confidence: 99%
“…The goal of this work is to show that this gap of 5 bits is too pessimistic and that it can be reduced to 1 bit with PDF with random switch [5]. In a companion paper we showed that Noisy Network Coding (NNC), proposed in [16] to reduce the gap of wireless FD multi-relay networks from 5(N + 2) [14] to 1.26(N + 2), can be used in HD multi-relay networks with random switch to reduce the gap from 5N [15] to 1.96(N + 2) [17].…”
Section: A Related Workmentioning
confidence: 99%